Отношение к прошлому - Сорока, Ю. (Iнститут соціології НАН України, 2009)
Ukraine is experiencing the transformation of symbolic space including symbols of the past. Such developments are brought up to date by different social agents' needs of self-identification. The past, history and memory are becoming an issue of social and humanitarian disciplines including sociology. The article is devoted to justifying the notion "attitude toward the past" defined as a perception of historical events and persons through adequate, available and legitimate symbols of the past in the course of spontaneous propositions, emotional evaluations, behavioural reactions, and production of cultural texts and opinions. This definition is based on critical analysis of M. Halbwax', P. Nora', P. Ricoeur', Th. Adorno conceptions about memory and the past. The meanings of the symbol of the past are multiple; individuals use and support these meanings according to their socio-cultural experiences, social positions, access to channels of meanings dissemination. According to data of mass survey, Ukrainian students' attitudes to the past demonstrate positive evaluation of distant historical persons, as well as differentiation of historical persons evaluation with respect to tradition / innovation contrasting and regional discrepancy concerning meaning - fulness of the past as a subject matter. However, the forming of common "pantheon" of Ukrainian heroes is also observed against this background.